SPRITUALITAS YESUS : MENGASIHI SESAMA SEPERTI MENGASIHI DIRI SENDIRI - Nur Fitriyana (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
The spirituality of Jesus in the first dimension, which is to love God with all your heart, soul and strength. This first dimension is perfected with a second dimension, loving one's neighbor as self-love. Implementation of this second dimension, that is, Jesus is consistent to say something related to the poor, the sick, the sinners, and the lost sheep of Israel